The Right to Education as a Catalyst for Economic Development - Odusote A, Abiodun Adeola (Unilag Journal of Humanities, 2019)
This study examines the effect of the enjoyment of the right to education on economic development. The study focuses on the role the right to education has to play in economic development. The study makes enquiries on the scope and content of the right to education and the correlation between the enjoyment of the right to education and economic development. The author finds that the enjoyment of the right to education produces a more educated society. To remain competitive in the contemporary and global marketplace and in the light of technological advancement, Nigeria needs to ensure that the right to education is assured. This will translate into an effective and competitive workforce. The study reveals that the Nigerian educational system is in dire need of reform, reform that will drive economic growth and educational advancement. Investing in national education has not been a top priority for different succeeding Nigerian governments for many years. Challenges include scarcity of textbooks, large classes, inadequate teaching materials, low staff morale and lack of competent teaching staff. This paper concludes that revitalising the education sector is a viable option for economic development in Nigeria.